Geophilosophy: from Nietzsche to geography - Oliveira Ferraz, Claudio Benito [UNESP] (Univ Federal Fluminense, 2017)
Gilles Deleuze and Felix Guattari claim that it was Friedrich Nietzsche who was the first modern philosopher to experience geographic force in the elaboration of thought and dominated this process of geophilosophy. From this perspective, this article focus the analysis of some elements the thought of Nietzsche and tries to highlight some of the effects of these in the constitution of a geographical reference plane. In this sense, the relation Earth/Territory will be worked from the perspective of the german philosopher and how it can instigate other possibilities for current geographic thinking.
Keywords: Geophilosophy; Earth; Territory; Difference